Two : the machine of political theology and the place of thought - Esposito, Roberto, 1950- (Commonalities., 2015)
"This book describes the historical underpinnings of political theology that continue to exert their influence. The confluence of Roman and Christian notions on the person fuels an exclusionary mechanism that unites by dividing people. Restoring thought to an impersonal place of universal access can help to end this oppressive conceptual regime"--